Selection and harvesting methods to breeding material for further creating collection of domestic pumpkins from Cucurbitaceae Juss. family (Experimental biology, 2016)
Over past centuries pumpkins due to their useful properties remained one of the most popular vegetable plants in the world. It has been established that seeds and preparations obtained from ripen pumpkins, possess membrane-stabilizing, anti-hypoxanthine, anti-hypertensive, anti-inflammatory, anti-allergic andanti-atherosclerotic impacts. They have also no contraindications and side effects to be thus recommended as a dietary supplements to food for children, pregnant and lactating women and elderly people. Issues relating to the creation of domestic pumpkin collection including food, feed and heirloom specimens invite a special attention in our country. To achieve this aim new methods of planning, treating seedlings with biofertilizer, and analysis of ripen pumpkin material have been developed.
Keywords: pumpkin; Cucurbitaceaejuss.; biofertilizer; hybrids.